Parking Functions and Related Combinatorial Structures. - Rattan, Amarpreet (University of Waterloo, 2001)
The central topic of this thesis is parking functions. We give a survey of some of the current literature concerning parking functions and focus on their interaction with other combinatorial objects; namely noncrossing partitions, hyperplane arrangements and tree inversions. In the final chapter, we discuss generalizations of both parking functions and the above structures.
Keywords: Mathematics; parking function; noncrossing partition; hyperplane arrangement; tree inversion